2022
DOI: 10.13057/biodiv/d231202
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and phenotypic characteristics of T1 transgenic yellow cosmos (Cosmos sulphureus) carrying neomycin phosphotransferase II gene

Abstract: Abstract. Irsyadi MB, Sawitri WD, Purwantoro A. 2022. Molecular and phenotypic characteristics of T1 transgenic yellow cosmos (Cosmos sulphureus) carrying neomycin phosphotransferase II gene. Biodiversitas 23: 6097-6105. Yellow cosmos (Cosmos sulphureus) is a tropical ornamental flower that contains secondary metabolites useful fornatural pesticide application. Plant genetic transformation is one genetic engineering method used to increase secondary metabolite accumulation. However, published reports on this i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Thus, the seedlings germinated had kanamycin resistance. The NPT II gene cannot inhibit protein synthesis and ribosome binding in transformant plants ( Irsyadi et al, 2022 ). However, the selected plants can be affected by their resistance properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the seedlings germinated had kanamycin resistance. The NPT II gene cannot inhibit protein synthesis and ribosome binding in transformant plants ( Irsyadi et al, 2022 ). However, the selected plants can be affected by their resistance properties.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the seedlings escaped at 50 ppm kanamycin concentration. Irsyadi et al (2022) reported that in 50 ppm kanamycin concentration, selected putative transformants of C. sulphureus that escaped kanamycin reached 3.84%. Dalton et al, (1995) reported the extremely low concentration of selective agents, which allowed the undesirably high numbers of escape and loss of resistant transformants.…”
Section: Discussionmentioning
confidence: 99%